2013
DOI: 10.5812/traumamon.10436
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Intertrochanteric Fractures: Dynamic Hip Screw versus Locking Compression Plate

Abstract: BackgroundAccording to the existing literature, the Dynamic Hip Screw (DHS) is the preferred standard for the treatment of intertrochanteric fractures. However, some surgeons use other devices such as the Locking Compression Plate (LCP).ObjectivesIn this study, we compared the outcome of using DHS or LCP in intertrochanteric fractures.Materials and MethodsThis cross-sectional study was carried out on 104 patients who were referred to Pursina Hospital in Rasht, Iran with intertrochanteric fractures of the femur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Outcomes were independent of gender and body mass index of patients; nonetheless, relatively poor functional and radiological outcomes were observed in diabetic and elderly patients (>65). Our findings are comparable to past studies such as Mardani-Kivi et al [23]. According to this study, DHS is a more reliable and successful treatment option in intertrochanteric fracture as compared to locking compression plate (LCP).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Outcomes were independent of gender and body mass index of patients; nonetheless, relatively poor functional and radiological outcomes were observed in diabetic and elderly patients (>65). Our findings are comparable to past studies such as Mardani-Kivi et al [23]. According to this study, DHS is a more reliable and successful treatment option in intertrochanteric fracture as compared to locking compression plate (LCP).…”
Section: Discussionsupporting
confidence: 91%
“…Incidences of device failure and limb shortening were comparatively lesser in DHS groups after six months of follow-up. Based on the Harris Hip Score, outcomes were classified as excellent in 31.7%, good in 63.3%, and fair in 5.0% of the patients [23]. Similarly, Shetty et al also reported good functional and radiological outcomes of DHS fixation of unstable intertrochanteric fractures with excellent to a good outcome in 59.4% as per the Harris Hip Score [24].…”
Section: Discussionmentioning
confidence: 99%
“…Govindasamy et al 6 reported mean Harris Hip Score 85.5 (83-94) with no poor result in 18 patients treated with PFLCP. Mohsen Mardani et al 24 reported Harris Hip Score 24 patients treated with DHS with stable fracture was 87.08 and for unstable fracture (36 patients) score was 84.61, while score for patients treated with PFLCP having stable fractures was 85.43 and with unstable fracture was 81.20.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of all hip fractures are intertrochanteric femoral fractures, defined as extracapsular fractures that occur between the greater and lesser trochanter of the proximal femur 3 . In patients over 50 years of age, more than 90% of hip fractures are intertrochanteric fractures with 20%-30% of these cases experiencing complications and a mortality rate of approximately 17% 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic hip screw (DHS) as an extramedullary construct or intramedullary nail with a cephalomedullary screw is the standard surgical treatment option chosen by most surgeons. There is literature about comparisons between these implants, including biomechanical characteristics, indications, complications, and outcomes 4,[6][7][8][9] . The recent consensus is that the implant options for the treatment of intertrochanteric fractures are closely related to the stability of the fractures 10,11 .…”
Section: Introductionmentioning
confidence: 99%